Mapping The Distribution Of Soil pH, Pyrite (FeS2) Content, Soil Texture, And Waterlogging In Rice Field Areas In Jejangkit District, Barito Kuala Regency - Akhmad Maki; Muhammad Efendi (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to identify the characteristics of soil pH, pyrite (FeS₂) content, soil texture, and waterlogging in rice fields in Jejangkit District, Barito Kuala Regency, map their spatial distribution using the Inverse Distance Weighting (IDW) method based on Geographic Information Systems (GIS), evaluate the accuracy of the interpolation results, and develop land management guidelines based on the physical conditions of the land. The study uses a quantitative approach with field survey methods and GIS-based spatial analysis. A total of 64 sample points are used as the main data for interpolation. The results show that the soil pH value ranges from 3.5–5.5, pyrite content is 0.3–4.4%, soil texture is dominated by clay fractions, while the height of waterlogging ranges from 14–64 cm. The IDW interpolation results are able to describe the spatial distribution pattern of all research parameters continuously. Validation testing shows that the interpolation results have a good level of accuracy so that they can be used to describe the condition of the research land.